MAPK signal pathways in the regulation of cell proliferation in mammalian cells - ZHANG, Wei; LIU, Hui Tu (Cell research, 2002)
ABSTRACT MAPK families play an important role in complex cellular programs like proliferation, differentiation, development, transformation, and apoptosis. At least three MAPK families have been characterized: extracellular signal-regulated kinase (ERK), Jun kinase (JNK/SAPK) and p38 MAPK. The above effects are fulfilled by regulation of cell cycle engine and other cell proliferation related proteins. In this paper we discussed their functions and cooperation with other signal pathways in regulation of cell proliferation.